Las plaquetas como modelo para el estudio de las enfermedades extrapiramidales - Bonilla, Ernesto (Investigación Clínica, 2013)
Several investigators have proposed that the platelet could be considered as a model for aminergic neurons. This proposition looks specially attractive for researchers working on CNS diseases. A detailed comparison of the kinetic, biochemical and pharmacologic properties seem to support the concept that platelets behave as serotonergic neurons but not as dopaminergic neurons. Therefore, studies on dopamine uptake by platelets of parkinsonian and choreic patients can not be extrapolated to pathologic alterations in the basal ganglia. Platelet serotonin uptake has been found to be normal in both diseases.